The Transient Response of Ice Volume to Orbital Forcing During the Warm Late Pliocene. Issue 20 (30th October 2017) - de Boer, Bas; Haywood, Alan M.; Dolan, Aisling M.; Hunter, Stephen J.; Prescott, Caroline L.
Abstract: Examining the nature of ice sheet and sea level response to past episodes of enhanced greenhouse gas forcing may help constrain future sea level change. Here, for the first time, we present the transient nature of ice sheets and sea level during the late Pliocene. The transient ice sheet predictions are forced by multiple climate snapshots derived from a climate model set up with late Pliocene boundary conditions, forced with different orbital forcing scenarios appropriate to two Marine Isotope Stages (MISs), MIS KM5c, and K1. Our results indicate that during MIS KM5c both the Antarctic and Greenland ice sheets contributed to sea level rise relative to present and were relatively stable. Insolation forcing between the hemispheres was out of phase during MIS K1 and led to an asynchronous response of ice volume globally. Therefore, when variations of precession were high, inferring the behavior of ice sheets from benthic isotope or sea level records is complex. Key Points: Simultaneous simulation of the GrIS and AIS over the warm Pliocene Pliocene time slice MIS KM5c displays limited ice volume fluctuations Asynchronous response in ice volume to orbital forcing during MIS K1